Queen's Royal College, Port of Spain, Trinidad, B.W.I. - Lanks, Herbert (My University, 2010)
Exterior view of the front of the Queen’s Royal College (QRC), situated at Maraval Road, Queen's Park West, Port of Spain, Trinidad. One of the main government secondary schools in Port of Spain, it was designed by Daniel M. Hahn, qualified architect and past student of QRC, and opened here 25 March, 1904, on lands that were once part of the government farm, St. Clair. In the foreground of this image are several school boys in uniform. As the time on the tower clock is 3:50 p.m. they are probably waiting to be collected from school by parents and guardians. Postcard number SC3232c.
Colour: Red, Blue, Black and White; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; [1970]; Cities and towns--Trinidad and Tobago--Port of Spain; Historic buildings--Trinidad and Tobago; Schools--Trinidad and Tobago; High schools--Trinidad and Tobago; Public schools--Trinidad and Tobago; Education, Secondary--Trinidad and Tobago; Architecture--Trinidad and Tobago; Architecture--Details; Towers--Trinidad and Tobago; Tower clocks--Trinidad and Tobago; Clocks and watches--Trinidad and Tobago; Windows--Trinidad and Tobago; Schoolboys--Trinidad and Tobago; School children--Trinidad and Tobago; School children's clothing--Trinidad and Tobago; Boys--Trinidad and Tobago; Bicycles--Trinidad and Tobago; Pants--Trinidad and Tobago; Shorts (Clothing)--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Uniforms--Trinidad and Tobago; Magnificent Seven, The (Port of Spain); Queen's Park Savannah (Port of Spain); Queen's Royal College (Trinidad and Tobago)